Інноваційні технології навчання англійської мови студентів університету - Панченко, Вікторія Валеріївна; Panchenko, Viktoriia V. (Східноєвропейський національний університет імені Лесі Українки, 2016)
Проблема оптимізації вивчення іноземної мови у вищих навчальних закладах шляхом застосування інноваційних технологій є надзвичайно актуальною і потребує нагального конструктивного вирішення. Розкрито зміст поняття інновації та інноваційної технології, подано їх характеристику та типи; проаналізовано найбільш продуктивні для вивчення англійської мови інноваційні технології; охарактеризовано інтерактивні методи навчання англійської мови студентів університету. Дослідження робить акцент на провідних компонентах змісту навчання англійської мови, на способах діяльності, тобто на навчанні різних видів мовленнєвої діяльності: говоріння, аудіювання, читання, письма. Наголошується, що інтерактивне навчання передбачає пізнання нового не від теорії до практики, а навпаки – від формування нового досвіду до його теоретичного осмислення через застосування, відійшовши від традиційної логіки навчального процесу. Узагальнено основні підходи до вирішення досліджуваної проблеми й окреслено шляхи її конструктивного вирішення. The article considers the importance of the innovative technologies in foreign languages teaching process and proves that they are extremely relevant, facilitate the optimization of learning a foreign language and require overall constructive solution and implementation. In the focus of attention is the analysis of innovative forms and methods of teaching English to university students. The article contributes to understanding of the most important issues of the problem under consideration and offers insights into the essence of innovative technologies, laying emphasis on the definition of the peculiarities of implementing them into teaching and learning English at university. The author concentrates on the analysis of the most effective innovative forms and methods used in the process of studying English at the university. In the article the content of innovation and innovative technology notions are considered; the most important their characteristics and types are highlighted on the basis of the analysis and selection of the most productive of them for teaching English. The selected by the author interactive methods of teaching English to university students are described in the article. In the conclusions to the article the author suggests some effective ways and forms to ensure the constructive solution of the problem under discussion and to make it beneficial for teaching and learning English at university.
Innovative Technologies in Teaching English to University Students
Keywords: інновація; педагогічна технологія; інноваційні технології; інтерактивні технології; інтерактивні методи навчання; навчання англійської мови студентів університету; innovation; educational technology; innovative technology; interactive technology; interactive teaching methods; teaching English to students of universities